JAV Lietuvių spaustuvės (iki 1904 m.) - Gargasaitė, Dalia (Knygotyra, 1983)
In the article there is a short review of the Lithuanian printing-houses activities in the USA. In 30 years a lot of p.-h. were founded. They printed on the whole during 1874–1904 years about 700 books and leaflets. The most productive of them were p.-h. of the newspaper “Vienybė lietuvninkų” in Plymouth, “Saulė” in Mahanoy City – both Pa., also the newspaper “Lietuva” in Chicago, III. The production of lithuanian p.-h. was destined for emigrants only partly. The part of circulation was sent to Lithuania, where since 1864 till 1904 years there was suppressed printing in Roman characters.